Differential preservation of children’s bones and teeth recovered from early medieval cemeteries: possible influences for the forensic recovery of non-adult skeletal remains - Manifold, Bernadette M. (Anthropological Review, 2013)
The skeletal preservation of 421 non-adult skeletons from four early medieval sites in England, Scotland and Wales were compared to assess whether geographical location and geology have an impact on overall bone preservation of children’s remains in the burial environment. Skeletons were examined from the cemeteries of Auldhame in Scotland, Edix Hill and Great Chesterford in England and Llandough in Wales. The bone preservation was examined using three preservational indices: Anatomical preservation index (API), Qualitative preservation index (QBI) and the bone representation index (BRI). A similar pattern existed across all the sites with regard to what bones are preserved, bones with relatively high density, such as the temporal bone of the skull, the long bones of the upper and lower limbs tend to be abundant in the samples, with the more small and fragile bones, such as the facial bones tending to be less well represented either as a result of low bone density or due to loss at excavation. The study of the dental elements also revealed a pattern with regard to what is preserved, with high numbers of molars and incisors found.This may be related to both the size and number of roots; but also the position in the mouth which may offer protection against loss. A difference in preservation was observed between the sites and the classes of preservation, particularly local differences between the sites of Edix Hill and Great Chesterford. From this study it remains unclear as to the extent the role of geology has on the non-adult skeleton, but the results of this study show that age is not the dominating factor in bone preservation as previously thought.